2017
DOI: 10.1021/acs.biochem.7b00228
|View full text |Cite
|
Sign up to set email alerts
|

Toggling of Diacylglycerol Affinity Correlates with Conformational Plasticity in C1 Domains

Abstract: Conserved homology-1 (C1) domains are peripheral membrane domains that target their host proteins to diacylglycerol (DAG)-containing membranes. It has been previously shown that a conservative aromatic mutation of a single residue in C1 has a profound effect on DAG affinity. We report that the “DAG-toggling” mutation changes the conformational dynamics of the loop region that forms the binding site for the C1 activators. Moreover, there is a correlation between the residue identity at the mutation site, DAG af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 19 publications
2
7
0
Order By: Relevance
“…the parameter that defines the intrinsic thresholds of DAG-mediated activation (Extended discussion 2). Our structural data (supported by previous NMR work [23][24][25] ) suggest that higher hydrophobicity and lipophilicity of Trp confers thermodynamic advantages and hence higher DAG-sensitivity to the C1B domains of novel PKC isoforms relative to conventional PKC isoforms that carry a Tyr at the equivalent position.…”
Section: Comparative Analyses Of the C1bd-agonist Structuressupporting
confidence: 81%
See 1 more Smart Citation
“…the parameter that defines the intrinsic thresholds of DAG-mediated activation (Extended discussion 2). Our structural data (supported by previous NMR work [23][24][25] ) suggest that higher hydrophobicity and lipophilicity of Trp confers thermodynamic advantages and hence higher DAG-sensitivity to the C1B domains of novel PKC isoforms relative to conventional PKC isoforms that carry a Tyr at the equivalent position.…”
Section: Comparative Analyses Of the C1bd-agonist Structuressupporting
confidence: 81%
“…According to solution NMR, this region undergoes conformational exchange on the µs-timescale 23,25 . Apo C1Bd was also crystallized under conditions similar to those for the C1Bd-DAG complex.…”
Section: Structure Of the C1bd-dag Complexmentioning
confidence: 99%
“…The most variable region is located between helix α1 and the C-terminal Cysteine residue that coordinates a structural Zn 2+ ion. According to solution NMR, this region undergoes conformational exchange on the μs-ms timescale 21 , 23 . We crystallized apo C1Bδ under conditions similar to those used for the C1Bδ-DAG complex (but without detergent) for a direct comparison.…”
Section: Resultsmentioning
confidence: 99%
“…A 13 C label was installed at the C12-OAc carbonyl position, and 2 H was incorporated as a CD 3 group on the C13-OAc, where the REDOR-determined distance would extend from the C12 carbonyl to the average position of the three deuterons ( Figure 1 B). Labeled ligands were complexed with a 51-residue peptide corresponding to the mouse PKCδ-C1b domain, 38 allowing comparison of previous structural studies 39 50 using this isoform domain, which recapitulates the ligand binding capabilities of the full-length protein. 51 The folding and function of PKC and its C1 domain are sensitive to its environment, and in the case of membrane-associated PKC, we have shown that the C1 domain does not fold properly for binding in water alone but only in association with a PS vesicle.…”
Section: Results and Discussionmentioning
confidence: 99%